2016
DOI: 10.1186/s12920-016-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and biologically relevant consensus strategy for Parkinson’s disease gene prioritization

Abstract: BackgroundThe systemic information enclosed in microarray data encodes relevant clues to overcome the poorly understood combination of genetic and environmental factors in Parkinson’s disease (PD), which represents the major obstacle to understand its pathogenesis and to develop disease-modifying therapeutics. While several gene prioritization approaches have been proposed, none dominate over the rest. Instead, hybrid approaches seem to outperform individual approaches.MethodsA consensus strategy is proposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 197 publications
(195 reference statements)
1
27
0
Order By: Relevance
“…In this work and similar to [33], we used some of the most extended metrics to estimate the enrichment ability in order to compare different gene prioritization strategies. The overall enrichment metrics include the area under the accumulation curve ( AUAC ); the area under the ROC curve ( ROC ); and the enrichment factor ( EF ) evaluated at the top 1, 5, 10 and 20% of the ranked list.…”
Section: Methodsmentioning
confidence: 99%
“…In this work and similar to [33], we used some of the most extended metrics to estimate the enrichment ability in order to compare different gene prioritization strategies. The overall enrichment metrics include the area under the accumulation curve ( AUAC ); the area under the ROC curve ( ROC ); and the enrichment factor ( EF ) evaluated at the top 1, 5, 10 and 20% of the ranked list.…”
Section: Methodsmentioning
confidence: 99%
“…When the levels of SNCA transcripts (which codes for α‐synuclein) were specifically investigated, differential gene expression between patients with PD and controls in both blood and brain were observed (Moran et al., ; Soreq et al., ; Simunovic et al., , ; Shehadeh et al., ; Soreq et al., ; Karlsson et al., ; Alieva et al., ; Infante et al., ; Nkiliza et al., ; Wang et al., ). Interestingly, these studies found decreased SNCA expression in patients with PD; whereas a few studies found no change (Kedmi et al., ; Durrenberger et al., ; Zhang et al., ; Cruz‐Monteagudo et al., ; Dumitriu et al., ; Kobo et al., ). This finding is contrary to what is expected from the literature about increased α‐synuclein protein expression in patients with PD and therefore warrants further investigation.…”
Section: Differential Expression Of Sncamentioning
confidence: 99%
“…When considering studies performed on the SN, the most prominent pathways which were consistently found to be altered in PD include dopamine metabolism, mitochondrial function, oxidative stress, protein degradation, neuroinflammation, vesicular transport and synaptic transmission (Table ; Table S1). Several studies reported a substantial downregulation of dopamine metabolism pathways, coupled with significantly decreased expression of key dopamine metabolism genes including the dopamine transporters; solute carrier family 6 member 3 ( SLC6A3) and solute carrier family 18 member A2 (SLC18A2) and dopamine decarboxylase (Grünblatt et al., ; Miller et al., ; Cruz‐Monteagudo et al., ). These findings have been interpreted to provide support for the involvement of dysregulated dopamine metabolism in PD pathogenesis; however, reports of decreased expression of dopamine metabolism genes are not surprising given the severe reduction in the number of surviving DA neurons in the SN of patients with PD.…”
Section: Common Differentially Expressed Genes and Pathways Identifiedmentioning
confidence: 99%
“…Parkinson’s disease (PD) - a neurodegenerative disorder which causes the death of dopaminergic neurons in the substantia nigra, causing tremors and postural instability - has been well-studied at the level of gene expression, with numerous microarray studies available in public repositories. Several meta-analyses of PD gene expression in human patients have been carried out [24] on datasets of up to 14 unique studies; however, concordance between these studies has been reported to be low even when standardized analysis is applied [36]. It has been proposed that discordance could result from different progression of the disease at time of post-mortem [6] and differing amounts of neuronal loss between the substantia nigra (SN) and other regions of the brain - indeed, an analysis of 11 human PD microarray studies demonstrated increased convergence within the five studies using samples from the SN [3].…”
Section: Introductionmentioning
confidence: 99%